IMPLEMENTASI INOVASI SISTEM PENGADUAN DALAM JARINGAN APLIKASI BEKASI ICONIC - Hakim, Moch Alif Taufiqul; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2021)
This study aims to explain the results of the implementation of the innovation of the Department of Communication and Informatics, Statistics and Encoding, Bekasi City, especially in online complaint services on the Bekasi Iconic application. To analyze it, this study uses the theory of policy implementation from George C. Edwards III with the variables of Communication, Resources, Disposition, and Bureaucratic Structure. In addition to policy implementation theory, this study also uses the theory of public service innovation. This study used a qualitative descriptive method with data collection techniques carried out through interviews. The results showed that, the implementation of services through the Bekasi Iconic application did not work based on the lack of good communication between regional apparatus, the absence of experts in the field of human resources at the Department of Communication, Informatics, Statistics, and Coded so that implementation was constrained, or lack of awareness. implementers in the implementation, and there is a change in the bureaucratic structure in the Office of Communication, Informatics, Statistics, and Encoding. In the online complaint service, there was a transfer of access channels through SP4N Report so that POT in 2020 is no longer used. In terms of bureaucratic behavior, the existence of budget cuts at each OPD has made the implementation of the Bekasi Iconic application in 2019 not running until now